Multifunctional properties and microstructural correlations of NiCoMnTi-Based high entropy alloys with focus on magnetic, thermodynamic, and radiation shielding characteristics - Ozkul, Iskender; Karaduman, Oktay; Simsek, Tuncay; Simsek, Telem; Canbay, Canan Aksu; Guler, Omer; Tekin, Huseyin Ozan (Springer Heidelberg, 2025)
High-entropy alloys (HEAs) are a novel class of materials known for their complex compositions and exceptional multifunctional properties. In this study, NiCoMnTi-based HEAs were modified with Fe, Cr, and Cu as fifth elements to systematically investigate their structural, magnetic, thermodynamic, and nuclear radiation shielding characteristics. The alloys were synthesized via arc melting and characterized using XRD, SEM-EDS, VSM, and theoretical modeling methods. The findings reveal that each additional element uniquely alters the alloy's properties. The Fe-containing alloy exhibited a well-defined lamellar microstructure, the highest saturation magnetization (10.79 emu/g), and a Curie temperature near 450 K, along with strong gamma-ray shielding performance across both low and high energy ranges. The Cr-containing alloy demonstrated soft magnetic behavior, featuring the lowest coercivity (29.64 Oe) and the highest fast neutron removal cross-section. In contrast, the Cu-containing alloy enhanced low-energy photon attenuation due to its higher atomic number but exhibited limited magnetic homogeneity. Despite these differences, all samples displayed stable thermodynamic behavior and comparable buildup factor trends. Overall, the addition of Fe led to a synergistic improvement in both magnetic and radiation shielding capabilities of the NiCoMnTi-based HEA system.
Keywords: High-entropy alloys (HEAs); NiCoMnTi-based alloys; Magnetocaloric effect; Microstructural characterization; Magnetic properties; Nuclear radiation shielding; Thermodynamic parameters